2012
DOI: 10.5539/elt.v5n8p185
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Washback Study of IELTS and TOEFL iBT on Teaching and Learning Activities in Preparation Courses in the Iranian Context

Abstract: One consequence of test use in the English-language teaching community is the negative washback of tests on teaching and learning. Test preparation courses are often seen as part of the more general issue of washback. IELTS and TOEFL iBT tests, focusing on communicative competence, are anticipated to have positive washback effect on how English is taught and learned. This study was a triangulation research to compare the washback of IELTS and TOEFL iBT on teaching and learning activities in test preparation co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
2
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 14 publications
1
2
0
4
Order By: Relevance
“…A study conducted in Iran has shown that mock tests can positively influence the training of IELTS candidates in the context of EFL. Erfani (2012) discovered that the ability to complete exams such as IELTS and TOEFL encouraged both language teachers and learners to use them as training tests in the classroom. Test-based language classes, however, have not always been preferred.…”
Section: Mock Testsmentioning
confidence: 99%
“…A study conducted in Iran has shown that mock tests can positively influence the training of IELTS candidates in the context of EFL. Erfani (2012) discovered that the ability to complete exams such as IELTS and TOEFL encouraged both language teachers and learners to use them as training tests in the classroom. Test-based language classes, however, have not always been preferred.…”
Section: Mock Testsmentioning
confidence: 99%
“…Nossa preocupação desde o início foi a de propor um curso em que ser aprovado no Celpe-Bras não fosse visto apenas como o único objetivo, mas como uma oportunidade para melhorar a proficiência em PLE dos alunos, indo além do mero fornecimento de materiais de prática para o teste, e criando oportunidades efetivas de desenvolvimento da produção oral de aprendizes de PLE em contexto online. Nesse sentido, corroboramos a visão de Erfani (2012) de que, em cursos preparatórios, os estudantes precisam realmente ter conhecimento sobre o construto e a estrutura do exame e suas implicações para o aprendizado; contudo, é necessário 2 a natural tendency for both students and teachers to tailor the classroom activities to the demands of the test, especially when the test is particularly important for test takers, and pass rates are used as a measure of teacher success. 3 […] tests are held to be powerful determiners of what happens in the classrooms.…”
Section: Introductionunclassified
“…Essa concepção de preparatório vai de encontro à do curso deste estudo, já que meu objetivo principal, desde o início, foi promover oportunidades de desenvolvimento oral e não apenas treinamento para o exame. Erfani (2012), em sua pesquisa sobre o efeito retroativo dos exames IELTS (International English Language Testing System) e TOEFL iBT® (Test of English as a 1 a natural tendency for both students and teachers to tailor the classroom activities to the demands of the test, especially when the test is particularly important for test takers, and pass rates are used as a measure of teacher success. 2 […] tests are held to be powerful determiners of what happens in the classrooms.…”
Section: Introductionunclassified
“…Em suas considerações finais, Erfani (2012) ressalta que, nesses cursos preparatórios, os estudantes precisam realmente ter conhecimento sobre o construto e a estrutura do exame e suas implicações para o aprendizado, contudo é necessário promover oportunidades para que eles possam ir além das exigências do teste, pois ao concentrar-se apenas em suas características e exigências, pode ser possível atingir boa pontuação sem, necessariamente, melhorar a capacidade linguística dos estudantes. Erfani, citando Green (2007), salienta também que estreitar o currículo de um curso para responder às demandas de um exame pode contribuir para uma distorção na interpretação dos resultados de um exame, podendo causar dúvidas em relação à sua validade.…”
Section: Introductionunclassified
See 1 more Smart Citation